Vocation and Destination in Kant’s Practical Philosophy - DiCenso, James (Con-Textos Kantianos. International Journal of Philosophy, 2019)
Kant frequently employs the German term Bestimmung in his mature work, and depending on context, this term can signify the Latin determinatio, vocatio, or destinatio. These three senses of Bestimmung are interconnected within Kant’s system of moral teleology. Bestimmung as determination expresses our wills as formed and regulated by the moral law, via the categorical imperative. Bestimmung as vocation guides us toward a determination of willing by rational principles based on the moral law, and this “call” is inseparable from our capacity to will and act autonomously under phenomenal and historical conditions. Bestimmung as “destination” conveys the ends toward which moral cultivation is directed, both individually and collectively. Understanding the three integrated uses of Bestimmung provides a clearer picture of the scope of Kantian ethics encapsulating the long-term goals toward which we are directed individually, as members of communities, and as human beings.